Quality deterioration of wet fish caught in Mymensingh farm in different steps of distribution channel towards Dhaka (Journal of the Bangladesh Agricultural University, 2013)
The fish landed for domestic consumption suffers from serious post harvest loss due to ignorance and negligence of the people involved in the harvest, distribution, processing and trade. Low quality fish is a constraint for food security and public health and is a cause for economic loss. The present study was carried out to identify the cause and to quantify the post harvest loss by a sensory tool. Quality deterioration of some major inland species of wet fish was determined at different steps of distribution channel from the fish farm gate of Mymensingh to Dhaka retail markets in June and July 2010. Five distribution channels i.e. farm gate, transport, arot (commission agent), wholesale and retail markets were studied to find out the deterioration level of the quality of fish. Data were collected by travelling with fish and from the stakeholders in distribution channel through questionnaire interviews. In the distribution channel of wet fish RRA and SWOT analysis were done with fish farmer, arotder, transporter, wholesaler and retailer. The major species studied were Indian major carps (Labeo rohita, Catla catla and Cirrhina mrigala), pangas (Pagasius sutchi), silver carp (Hypopthalmichthys molitrix) and tilapia (Oriochromis niloticus). Different species showed different levels of deterioration of quality at various steps of distribution channels. The quality of fish was found to be changed in between arot and retail market. Inadequate knowledge and practice in handling, icing and container use were found to be the major bottlenecks to keep the fish in acceptable quality.DOI: http://dx.doi.org/10.3329/jbau.v10i2.14926 J. Bangladesh Agril. Univ. 10(2): 331-337, 2012